Faktor Kualitas Produk, Harga, dan Promosi Dalam Keputusan Pembelian Le Minerale Pada Mahasiswa Yogyakarta - Yunus Siwa jurumana; Muhammad Mathori (CV. ITTC INDONESIA, 2026)
This study aims to analyze the influence of product quality, price, and promotion on purchasing decisions of Le Minerale bottled drinking water among university students in the Special Region of Yogyakarta. This research uses a quantitative approach with data collected through questionnaires distributed to 100 student respondents who have consumed Le Minerale. Data were analyzed using multiple linear regression with SPSS version 26. The results show that partially, price and promotion have a positive and significant effect on purchasing decisions, while product quality does not have a significant effect. Simultaneously, product quality, price, and promotion significantly influence purchasing decisions. The Adjusted R² value of 0.261 indicates that 26.1% of the variation in purchasing decisions can be explained by the three independent variables, while the remaining 73.9% is influenced by other factors outside the model. These findings indicate that students tend to perceive bottled drinking water as a standardized product, making price suitability and promotional attractiveness more decisive than technical product quality.